2018
DOI: 10.1051/0004-6361/201833052
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of the protocluster of galaxies around 7C 1756+6520 at z ~ 1.4

Abstract: Aims. The aim of this paper is the spectroscopic study of 13 galaxies belonging to the field of the protocluster associated with the radio galaxy 7C 1756+6520 at z = 1.4156. In particular, we focus on the characterization of the nuclear activity.Methods. This analysis has been performed on rest-frame optical spectra taken with the Large Binocular Telescope, using the spectrograph LUCI, which is operative in the near-infrared domain. The adopted spectral coverage allowed us to observe emission lines such as Hα,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 194 publications
(232 reference statements)
0
1
0
Order By: Relevance
“…This evidence seems to suggest a crucial role of AGN in the galaxy evolution at this epoch and for these environments. The discovery of multiple AGN activity is common in proto-clusters, where large centrally over-density of AGN are frequently found (Digby-North et al 2010;Galametz et al 2010;Krishnan et al 2017;Casasola et al 2018), but up to now only few works reported multiple AGN activity in high-z galaxy cluster cores, although not at such small distances. For example, Hilton et al (2010) reported the detection of two central X-ray cluster member AGN at a projected distance of ≈90 kpc in the z = 1.46 galaxy cluster XMMXCS J2215.9-1738 and, at higher redshift (z∼2), Gobat et al (2013) found two X-ray AGN at a projected distance of ∼100 kpc in CL J1449+0856.…”
Section: Multiple Agn Activity In the Cluster Corementioning
confidence: 99%
“…This evidence seems to suggest a crucial role of AGN in the galaxy evolution at this epoch and for these environments. The discovery of multiple AGN activity is common in proto-clusters, where large centrally over-density of AGN are frequently found (Digby-North et al 2010;Galametz et al 2010;Krishnan et al 2017;Casasola et al 2018), but up to now only few works reported multiple AGN activity in high-z galaxy cluster cores, although not at such small distances. For example, Hilton et al (2010) reported the detection of two central X-ray cluster member AGN at a projected distance of ≈90 kpc in the z = 1.46 galaxy cluster XMMXCS J2215.9-1738 and, at higher redshift (z∼2), Gobat et al (2013) found two X-ray AGN at a projected distance of ∼100 kpc in CL J1449+0856.…”
Section: Multiple Agn Activity In the Cluster Corementioning
confidence: 99%